PTU-021 Efficacy, Safety and Complications of Endoscopic Submucosal Dissection for Colonic Lesions in the Very Elderly Patients above Eighty Years of Age. (17th August 2016) - Woo, J; Matsuoka, J; Kowazaki, Y; Nishimura, M
Abstract : Introduction: Endoscopic submucosal dissection (ESD) has been safely utilised for resection of colonic lesions. 1, 2 More evidence is required in determining the safety profile of ESD in colonic lesion resection, particularly in the super elderly patients ≥80 years of age. In Japan, ESD is approved for both large adenomatous and superficial neoplastic lesions. Our hospital has been a centre for elderly gastroenterology care in North Western Tokyo, and has been an established ESD centre since 2013. The aim of this study is to provide further comparative data on the safety and feasibility of ESD provision in elderly patients ≥80 years of age. Methods: A single centre retrospective analysis of our hospital's ESD database was undertaken. Patients had ESD performed for colonic lesions from July 2013 till December 2015 were included and divided into 2 groups-either ≥80 years old or <80 years old. Data on baseline characteristics (age, sex, comorbidity), ESD procedure data, complications and specimen histology were analysed and compared. Results: A total of 119 patients were included in this study of which 41 (34%) were ≥80 years of age and 78 (66%) were <80 years old. Baseline comorbidity were indifferent between the two groups (p = 0.49). All complications recorded including bleeding, hypo/hypertension, desaturation and tachy/bradyarrythmia were all successfully corrected during the ESD procedure. Bleeding episodes were treated with needle knife coagulation and/or coagrasper. Post ESD, 2.5% of ≥80 group and 4% of the < 80 age group experienced bleeding requiring urgent endoscopy. All cases of post ESD bleeding occurred within 24 hours post ESD, and were all successfully treated endoscopically without subsequent rebleed. There was no peforation, followup surgery or intensive-care admission reported. Overall, no major adverse events reported during or post ESD. A colonic ESD video is included for demonstration. Conclusion: ESD is a safe and minimally invasive procedure for resection of colonic lesions even in elderly patients above 80 years of age. In addition to an excellent en-bloc resection rate, direct visualisation of the submucosal layer during the dissection process in experienced operators allows a safer and virtually perforation free resection. References: 1 Tamegai Y, Saito Y, et al . Endoscopic submucosal dissection: a safe technique for colorectal tumours. Endoscopy . 2007;39 (5):418–422. 2 Saito Y, Uraoka, et al . Endoscopic treatment of large superficial colorectal tumours: a case series of 200 endoscopic submucosal dissections. GI Endoscopy 2007;66 (5):966–73. Disclosure of Interest: None Declared